Cracked monolayer 1T MoS2 with abundant active sites for enhanced electrocatalytic hydrogen evolution. Issue 3 (25th January 2017) - Li, Yue; Wang, Longlu; Zhang, Shuqu; Dong, Xueru; Song, Yuze; Cai, Tao; Liu, Yutang
Abstract : Cracked monolayer 1T MoS2 with a porous structure was successfully prepared and exhibited excellent HER performance. Abstract : Molybdenum disulfide (MoS2 ) is a promising non-precious-metal catalyst, but its performance is limited by its density of active sites and poor electrical transport. Here, we report the design and preparation of cracked monolayer 1T MoS2 with a porous structure through the ultrasonication enhanced lithium intercalation of hydrothermally synthesized MoS2 nanosheets. The unique resulting catalyst can have more active sites introduced via the formation of porosity within the monolayer nanosheet, and the electrical transport ability can be increased through the change in electronic states from semiconducting in the 2H phase to metallic in the 1T phase. As is expected, the cracked monolayer 1T MoS2 exhibited good durability and an excellent hydrogen evolution reaction performance with a low overpotential (at 10 mA cm −2 ) of 156 mV (V vs. RHE) in acid media and a small Tafel slope of 42.7 mV dec −1 . This work will provide an intriguing and effective approach to designing electrocatalysts based on MoS2 or other layered materials with enhanced HER performance.